Antibacterial Activity Assay of 96% Ethanol Extract of Strawberry Leaves (Fragaria × ananassa Duch.) Against Streptococcus mutans Using the Disc Diffusion Method and Phytochemical Analysis - Mahfur, Mahfur; Adelina, Priatin Nova (Jurnal Biologi Tropis, 2026)
Abesah, N. H. S., & Mahfur, M. (2024). Isolasi dan identifikasi antioksidan jamur endofit umbi talas (Colocasia esculenta (L.) Schott) menggunakan pereaksi semprot DPPH secara bioautografi. Jurnal Insan Farmasi Indonesia, 7(3), 367–378. https://doi.org/10.36387/jifi.v7i3.2235 Allo. (2016). Uji aktivitas antibakteri dari ekstrak air kulit buah pisang Ambon lumut (Musa acuminata Colla) terhadap pertumbuhan Staphylococcus aureus (Skripsi). Universitas Sanata Dharma. Andesmora, E. V., Muhadiono, M., & Hilwan, I. (2017). Ethnobotanical study of plants used by people in Hiang Indigenous Forest, Kerinci, Jambi. Journal of Tropical Life Science, 7(2), 95–101. Bakti, T. E. K., & Mahfur, M. (2023). Skrining fitokimia dan analisis kadar flavonoid total fraksi etil asetat kulit buah durian merah (Durio graveolens Becc.) dengan metode spektrofotometri UV–Vis. Journal of Pharmacy Science and Technology, 4(1), 30–35. https://doi.org/10.30649/pst.v4i1.57 Bouyahya, A., et al. (2016). Determination of phenolic contents, antioxidant and antibacterial activities of strawberry tree (Arbutus unedo L.) leaf extracts. British Biotechnology Journal, 14(3), 1–10. https://doi.org/10.9734/BBJ/2016/26488 Elfeky, N., Mohamed Mousa, A. M., Abdelsameea Mahmoud, E., Mohammed Awad, S., El-Sabbagh, S. M., & Zayed, M. (2023). Antimicrobial activities of Fragaria × ananassa leaves against multidrug-resistant Acinetobacter baumannii. Delta Journal of Science, 47(1), 154–170. https://doi.org/10.21608/djs.2023.231555.1127 Engleberg, N. C., DiRita, V., & Dermody, T. S. (2006). Schaechter's mechanisms of microbial disease (4th ed.). Lippincott Williams & Wilkins. Fajrina, A., Jubahar, J., & Hardiana, N. (2017). Uji aktivitas fraksi dari ekstrak akar kangkung (Ipomoea aquatica Forssk.) terhadap bakteri Streptococcus mutans. Jurnal Farmasi Higea, 9(2). (DOI yang dicantumkan perlu diverifikasi karena tidak sesuai dengan jurnal). Ginting, M., Ginting, P., & Sari, S. A. (2023). Studi aktivitas antibakteri ekstrak etanol daun stroberi (Fragaria × ananassa (Weston) Rozier) terhadap bakteri Propionibacterium acnes. Journal of Pharmaceutical and Sciences, 6(1), 281–286. https://doi.org/10.36490/journal-jps.com.v6i1.56 He, M., Huang, Y., Wang, J., Chen, Z., Xie, J., Cui, Z., et al. (2025). Advances in polysaccharide-based antibacterial materials. International Journal of Biological Macromolecules, 308, 142598. (DOI perlu diverifikasi karena DOI yang dicantumkan mengarah ke jurnal lain.) Hirsch, M., Burges, P. L., Migueliz, L., Villarreal, N. M., & Marina, M. (2024). Isolation of beneficial bacteria from strawberry (Fragaria × ananassa Duch.): Potentialities for fungal disease control and plant growth promotion. Plant Growth Regulation, 102(1), 135–152. Jannah, A., Rachmawaty, D. U., & Maunatin, A. (2017). Uji aktivitas antibakteri ekstrak etanol, etil asetat, dan petroleum eter rambut jagung manis (Zea mays saccharata Sturt) terhadap bakteri Staphylococcus aureus dan Escherichia coli. Alchemy: Journal of Chemistry, 5(4). Kaur, A., Goindi, S., & Katare, O. P. (2016). Thermal analysis and quantitative characterization of compatibility between diflunisal and lipid excipients as raw materials for development of solid lipid nanoparticles. Thermochimica Acta, 643, 23–32. Mahfur, M. (2016). Uji sitotoksik fraksi etil asetat ekstrak etanol akar pasak bumi (Eurycoma longifolia Jack) terhadap sel kanker T47D dengan metode MTT. Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 30(2), 57–64. https://doi.org/10.31941/jurnalpena.v30i2.497 Mahfur, M., Khasanah, K., Anindhita, M. A., Chandra, S. G., & Hidayah, A. N. (2023). Comparison of the total phenolic and flavonoid contents of Amomum compactum Sol. ex Maton from Linggo Asri and Paninggaran Districts, Pekalongan Regency. Sasambo Journal of Pharmacy, 4(1), 8–13. https://doi.org/10.29303/sjp.v4i1.212 Mahfur, M., Kamila, A., Abidah, J. F., Samirana, P. O., Hikmawan, B. D., & Pratimasari, D. (2023). Antibacterial activity of ethyl acetate extract of symbiont fungus Aspergillus sp. in the sponge Rhabdastrella sp. from Gili Layar Island, Lombok, Indonesia. Journal of Applied Pharmaceutical Science, 13(11), 144–151. https://doi.org/10.7324/japs.2023.146303 Mahnashi, M. H., & Alshehri, O. M. (2022). Isolation, in vitro and in silico anti-Alzheimer and anti-inflammatory studies on phytosteroids from aerial parts of Fragaria × ananassa Duch. Biomolecules, 12(10), 1430. Mazurel, D., Brandt, B. W., Boomsma, M., Crielaard, W., Lagerweij, M., Exterkate, R. A. M., & Deng, D. M. (2025). Streptococcus mutans and caries: A systematic review and meta-analysis. Journal of Dental Research, 104(6), 594–603. Rani, K., & Mahfur, M. (2023). Analisis kadar flavonoid total ekstrak bonggol pisang kepok kuning (Musa acuminata Colla) secara spektrofotometri UV–Vis. Benzena Pharmaceutical Scientific Journal, 2(1). (Halaman perlu dilengkapi.) Rusmalina, S., Mahfur, M., Ermawati, N., Maliah, N., Ananda, L., Pratama, K. B., et al. (2025). The optimization of fermentation for metabolite production by symbiont Penicillium nalgiovense from the sponge Gelliodes fibulata. Medical Sains: Jurnal Ilmiah Kefarmasian, 10(1), 9–18. https://doi.org/10.37874/ms.v10i1.1682 Salas-Arias, K., Irías-Mata, A., Sánchez-Kopper, A., Hernández-Moncada, R., Salas-Morgan, B., Villalta-Romero, F., & Calvo-Castro, L. A. (2023). Strawberry (Fragaria × ananassa cv. Festival): A polyphenol-based phytochemical characterization in fruit and leaf extracts. Molecules, 28(4), 1865. https://doi.org/10.3390/molecules28041865 Widyaningtias, et al. (2014). Uji aktivitas antibakteri ekstrak terpurifikasi daun sirih hijau (Piper betle L.) terhadap bakteri Propionibacterium acnes. Jurnal Farmasi Udayana, 3(1), 50–57. (Volume, nomor, dan halaman perlu diverifikasi.) Widiatmoko, H. (2016). Sehat tanpa obat dengan si merah stroberi. Rapha Publishing. Ye, D., Liu, Y., Li, J., Zhou, J., Cao, J., Wu, Y., et al. (2025). Competitive dynamics and balance between Streptococcus mutans and commensal streptococci in oral microecology. Critical Reviews in Microbiology, 51(3), 532–543. Zhou, Y., Chen, X., Chen, T., & Chen, X. (2022). A review of the antibacterial activity and mechanisms of plant polysaccharides. Trends in Food Science & Technology, 123, 264–280. https://doi.org/10.1016/j.tifs.2022.03.020